AUTOMATICALLY CONTROL LIGHT INTENSITY WITH GOOGLE VOICE ASSISTANT COMMANDS - Amar Rasuli; Akhmad Ahfas; Izza Anshory (Media Bina Ilmiah, 2023)
Everyday light is the most important part to support human activity. Inadequate light quality can harm visual function, thinking, productivity, and human work activities. Therefore we need a tool that can adjust the intensity of light. This research realizes several human activities that can adjust the light intensity with google voice assistant commands using a smartphone. ESP32 is used as a connecting device between the Google voice assistant and the AC light dimmer module. In addition, this tool can be controlled remotely to all corners of the world because it uses the blynk API and is connected to the internet network. Based on the results of the tests that have been carried out, on the command "mati" the lamp voltage is 3.6 volts with a light intensity of 0 lux, on the command "sleep" the lamp voltage is 107 volts with a light intensity of 1604.4 lux, on the command "Santai" the lamp voltage is 161, 8 volts with a light intensity of 2416.4 lux and on the command "learn" the lamp voltage is 216.6 volts with a light intensity of 3603 lux.